Chronic fibrosing pulmonary aspergillosis: a cause of 'destroyed lung' syndrome. Issue 4 (3rd April 2017) - Kosmidis, Chris; Newton, Pippa; Muldoon, Eavan G.; Denning, David W.
Abstract: Background: Chronic pulmonary aspergillosis (CPA) has substantial impact on quality of life. A subset of patients develops significant pulmonary fibrosis, identified either on biopsy or radiologically. The term chronic fibrosing pulmonary aspergillosis (CFPA) has been suggested. Methods: We describe 11 patients with CFPA referred to our centre. Results: Mean age was 58.5 years and five were male. In nine, fibrosis was already evident on presentation, while in two it developed 3 and 6 years later. The predominant radiological feature was extensive or complete involvement of the entire lung, with minimal contralateral involvement. All patients received prolonged antifungal treatment. Two patients had surgical treatment; both developed post-operative complications. The contralateral lung remained free of significant disease in all but three patients. Conclusions: CFPA is a rare complication of CPA that is usually evident on presentation, but may develop after years in patients not on antifungals. Fibrosis resembles the 'destroyed lung' syndrome described after treated tuberculosis.